Improving writing recount texts through semantic mapping - Purwanto Purwanto (Teacher in Educational Research, 2019)
The research was conducted with the aim of to applying semantic mapping to improve students’ ability in writing recount texts of the second grade of SMPN 1 Metro Lampung.This was a classroom action research which was conducted in two cycles. Each cycle consisted four stages: planning, acting, observing, and reflecting. The research subjects were 25 students-nine boy students and sixteen girl students. The data were collected through observations, tests, and questionnaires. The research instruments consisted of observation sheet, tests, and questionnaires. The data from the observations and the learning achievement tests were analyzed using the quantitative technique. The success indicator in this study is that the students’ writing skill improves if, in terms of the learning mastery in the writing skill, of the students scored at least 80. This research shows that the use of semantic mapping improves the students’ writing ability in grade VIII.1 students of SMPN 1 Metro Lampung. The improvement is seen from the results of observation and students’ writing tests. The observation result shows that the students’ activeness in cycle I is middle and the students’ activeness in cycle II is high. Based on the results of students’ writing scores, the mean score of the pretest is 64,08, the mean score  of the first cycle is 80.48, and the mean score in cycle 2  is 88.60. From those results, it can be concluded that semantic mapping strategy can improve the students’ writing in the recount texts.